Reinforcing Student Learning Experiences in Biochemistry through Podcasts and Mobile Learning - Hartfield, Perry (INTI University College, 2009)
This paper presents evidence from a pilot podcasting study undertaken in 2007 and 2008 in a core biochemistry unit within the course structures of applied science, nutrition and human movement studies degree programs. The alms of the study were to generate educational podcast resources that reinforced conceptual teaching and learning in biochemistry and determine students’ attitudes to the perceived usefulness and benefit of educational podcasts. Podcasts were recorded (MP3 audio files) separately from the didactic lecture program in biochemistry. Subsequent to the weekly lecture, podcasts were integrated within the resources presented to students through their learning management system (Blackboard) and made available through RSS feeds. The vast majority (>88%) of students utilized the podcast resources, Indicating a high level of uptake for this portable educational technology amongst the student cohort. The respondents reported that podcasts focused their attention to core learning concepts and supported their understanding and learning of the lecture materiel, in addition, the survey data showed that respondents agreed strongly that podcast resources assisted with study and revision for examinations and, somewhat surprisingly, there was a perception that podcasts positively impacted on examination performance. Overall, student users perceived that educational pod casting could be used as an effective and valuable tool for their Learning and understanding of biochemistry.